(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The arrival of a woman is like the first light of dawn, dispelling the shadows. She has the power to dispel any anxiety that arises from mental shadows, like the sun that illuminates the world. Essentially, life begins with women. The fact that women are the ones who brought this universe into being is an undeniable fact. A strong belief in women’s inherent worth as human beings is fundamental to feminism. It identifies shifts in cultural norms that repress women and works to alter those norms. Feminism examines and analyses the repressed position of women in a socio-political setting by pursuing such an effort. Equal rights and status for women are the goals of this movement. The Indian author Mulk Raj Anand also wrote short stories. The Indian social fabric is something that Arundhati Rao has a keen eye for. As a revolutionary spark for the litterateurs of the twenty-first century, he fights for the rights of the marginalised and oppressed. In his books, Anand depicts the impoverished people of India in a realistic light. This article uses Arundhati Rao’s The Ministry of Utmost Happiness (2017) as a lens through which to examine Mulk Raj Anand’s 1960 novel The Old Woman and the Cow via the feminist topic of gender inequalities. There is a noticeable trend in modern English-language literature towards works written by Indian women. From a societal and personal perspective, this study examines the achievements of Indian women.